An experimental examination of the role of turbulence on flame impingement heat transfer. (15th May 2020) - Zhen, H.S.; Zhang, T.Y.; Wei, Z.L.; Chen, Z.B.; Huang, Z.H.; Leung, C.W.
Abstract: Turbulence induced by actuators has been widely utilized as a effective means to enhance jet impingement heat transfer (JIHT). Flame impingement heat transfer (FIHT) has parital similarity to JIHT, and thus it is of interest to investigate the role of an actuator-induced turbulence to flame combustion as well as its FIHT. On a Bunsen burner that is incorporable with a ring-type turbulence actuator, a detailed experimental comparison of the flame appearance, reaction zone structure, thermal field and heat transfer of both laminar and turbulent flames under identical bulk flow conditions and equivalence ratios were conducted. Results show that the turbulent flame has a narrower stable-operation range than the laminar couterpart, and thus turbulence reduces the flame stability. A major difference between two flames exists at the reaction zone, which is identified to be a 'brush' structure in the turbulent case, instead of being a perfect cone in the laminar case. The flame brush changes the heat release behavior such that the temperature field of the turbulent flame shows lowered peak temperature while enlarged high-temperature zone. The changed heat release or temperature field reults in distinct local heat fluxes in the impinging flames at the stagnation region and near wall jet region. Consequently, the overall heat transfer rate of the turbulent flame becomes higher than the laminar flame. Accordingly, this study proposes that the actuator turbulence can be utilized as a useful technique to promote FIHT.